COVID-19 is associated with a high prevalence of liver damage: a systematic review and meta-analysis (Journal of Patan Academy of Health Sciences, 2021)
Introduction: The Coronavirus Disease 2019 (COVID-19) outbreak is a serious threat to humans, and the impact of COVID-19 on the liver remains unexplored. At present, no meta-analysis has summarized available findings of COVID-19 patients with liver injury in depth. Thus, we aimed to scrutinize the association of the liver in COVID-19 patients and approximate the prognosis of COVID-19 patients with liver injury thoroughly.Method: We searched different databases for qualified studies between December 2019 to May 2021. Finally, meta-analysis was carried out using fixed-effect or random-effect models based on the heterogeneity.Result: Our Meta-analysis includes 32 studies with a total of 6,933 COVID-19 patients. The pooled prevalence of chronic liver disease (CLD) was 3.5%. Overall, the rates of severity and mortality in COVID-19 patients with underlying CLD were 4.6% and 19.2%, respectively. Additionally, the incidence of acute on chronic failure (ACLF) among COVID-19 patients with CLD was 25.1%. The prevalence of an increase in serum ALT, AST, TBil, and LDH levels was 39.5%, 28.6%, 26.5%, and 55.5%, respectively. Similarly, PT was prolonged in 8.3% of cases, and albumin was decreased in 66.8% of cases. The pooled prevalence of liver injury among COVID-19 patients was 28.2%. Strikingly, the patients with liver injury had significantly more severe disease (42.3%) and a higher incidence of mortality (18.5%) than the patients without liver injury.Conclusion: In conclusion, more than one in five of the COVID-19 patients is at risk of developing a liver injury. Further, patients with liver injury have significantly more severe disease and a higher incidence of mortality than patients without liver injury. Thus, careful monitoring of liver function is advisable while treating COVID-19 patients.